PEMETAAN KEBUTUHAN GURU GEOGRAFI TINGKAT SEKOLAH MENENGAH ATAS (SMA) - Irafitriana Sulistiawati; Pargito Pargito; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2013)
This study aims to descibe the state of a geography teacher to calculate and to map the needs of geography teacher and its relevance with the educational background of high school geography teacher in Ogan Komering Ulu distict, Sumatera Selatan in 2012. This study used descriptive methode as the research method, while the data collection techniques used were koesioner and documentation. The technical data analysis used was descriptive analysis. The population in this study were 27 high schools in Ogan Komering Ulu district. These results indicate:1). The number of high school geography teacher in OKU is 34 people consisting of 13 teacher-sex male, 21 female teachers, 11 permanent teachers, 23 teacher salaries and only 16 teachers who have certification. The Media of teaching is often used by geography teacher in OKU are maps and globes, added by media images, and video. The material that most difficult to understand were the 20 teachers choose materials GIS and remote sensing, 1 person chose material antroposfer and 14 teachers have no trouble. 2). The need for high school geography teacher is 33 geography teacher. 3). Schools that exceeds 1 geography teacher are Sentosa Bhakti senior high school and Kader Pembangunan senior high school that located in Baturaja Timur sub-district. Then only Senior High School number 8 OKU,located in Sinar Peninjauan sub-district, is lack of 1 geography teacher. 4). The relevance of the educational background of teachers are only 16 geography teacher were graduate of S1 Geography Education, 17 teachers were graduate of S1 Non Educational geography and 1 teacher is graduate of SMEA. So we can say that the total shortages of geography teachers in OKU district based on the relevance of the educational background above ie 17 teachers.Keyword:  Mapping, Geography Teachers Need